Preparation of polymer cement adhesive (PCA) by dry construction mixtures technology (DCT) (Международный научный журнал «Инженер», 2026)
In the article the properties of polymer cement adhesive obtained by the technology of DCT are investigated and the methods of testing and technological schemes of obtaining DCT are given, also rational duration of obtaining dry mixture is established and it is shown that at the content of sand filler with Sud. 1000 cm2/g - 50%, hyperplasticiser POLIMIXJBI - 1,0% it is possible to obtain PCA with required cohesive strength.